Lire la communication-monde au XXIe siècle - Cabedoche, Bertrand (Hors collection, 2023)
How can we grasp global communication issues when the term communication internationale is being instrumentalized by a most diverse range of actors? By contrast, Lire la communication-monde au xxie siècle offers a structured reading of contemporary cross-border issues, to the point of decentring.